LITERATURE REVIEW OF THE APPLICATION FRAMEWORK IN THE ENTERPRISE ARCHITECTURE OF SECONDARY SCHOOLS - Lubis, Rivaldi; Panjaitan, Erwin Setiawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2024)
Abstract: The widespread use of information and communication technology (ICT) has enhanced effectiveness and quality in management, research, and education at educational institutions. In this digital age, secondary schools are required to improve operational efficiency and educational strategies through the use of information technology. Therefore, the implementation of an enterprise architecture (EA) framework is crucial to ensure a strategic alignment between educational goals and technology. However, before implementing the framework, schools must evaluate various factors that influence the suitability and effectiveness of EA, including current technology needs, staff competencies, existing infrastructure conditions, and other factors. This study gathers and analyzes data from related studies, and the results indicate the importance of understanding EA principles to optimize academic and administrative processes. By considering variables in the selection of the EA framework, evaluating school readiness, and identifying existing challenges, this research aims to assist secondary schools in effectively implementing EA. The expected outcome of this research provides theoretical support for the adoption of EA, thus facilitating more efficient strategic and operational planning in secondary schools. Keywords: enterprise architecture; framework; information and communication technology; secondary school. Abstrak: Penggunaan teknologi informasi dan komunikasi (TIK) secara luas telah meningkatkan efektivitas dan kualitas dalam manajemen, penelitian, dan pendidikan di institusi pendidikan. Di era digital ini, sekolah menengah dituntut untuk meningkatkan efisiensi operasional dan strategi pendidikan melalui pemanfaatan teknologi informasi. Oleh karena itu, penerapan framework arsitektur enterprise (EA) menjadi penting untuk memastikan aliansi strategis antara tujuan pendidikan dan teknologi. Namun, sebelum penerapan framework dilakukan, sekolah harus mengevaluasi berbagai faktor yang mempengaruhi kesesuaian dan efektivitas EA, termasuk kebutuhan teknologi terkini, kompetensi staf, kondisi infrastruktur yang ada, dan faktor lainnya. Penelitian ini mengumpulkan dan menganalisis data dari studi terkait, hasilnya menunjukkan bahwa pentingnya pemahaman tentang prinsip-prinsip EA untuk mengoptimalkan proses akademik dan administratif. Dengan mempertimbangkan variabel-variabel dalam pemilihan framework EA, evaluasi kesiapan sekolah, dan identifikasi tantangan yang ada, penelitian ini bertujuan untuk membantu sekolah menengah dalam mengimplementasikan EA secara efektif. Diharapkan hasil dari penelitian ini memberikan kontribusi teoretis yang mendukung pengadopsian EA, sehingga memfasilitasi perencanaan strategis dan operasional yang lebih efisien di sekolah menengah.Kata kunci:arsitektur enterprise; framework; sekolah menengah; teknologi informasi dan komunikasi.